2021
DOI: 10.3390/s21144724
|View full text |Cite
|
Sign up to set email alerts
|

Scattered Far-Field Sampling in Multi-Static Multi-Frequency Configuration

Abstract: This paper deals with an inverse scattering problem under a linearized scattering model for a multi-static/multi-frequency configuration. The focus is on the determination of a sampling strategy that allows the reduction of the number of measurement points and frequencies and at the same time keeping the same achievable performance in the reconstructions as for full data acquisition. For the sake of simplicity, a 2D scalar geometry is addressed, and the scattered far-field data are collected. The relevant scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the previous section, we concluded that devising a data sampling strategy is equivalent to finding a proper quadrature role to approximate the integral representation of ps f adj . In the event that the measurement domain is in the far field [47], or even when the Fresnel paraxial approximation works [28], the matter is relatively straightforward, since the scattering operator can be given in terms of a Fourier transform and the data can be sampled according to the Nyquist sampling rate. When far-field conditions or the Fresnel approximations do not hold, the spatial frequency band of the scattered field can be estimated by invoking stationary phase arguments and the Nyquist step set accordingly (as shown in [34,35,48]).…”
Section: The Warping Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous section, we concluded that devising a data sampling strategy is equivalent to finding a proper quadrature role to approximate the integral representation of ps f adj . In the event that the measurement domain is in the far field [47], or even when the Fresnel paraxial approximation works [28], the matter is relatively straightforward, since the scattering operator can be given in terms of a Fourier transform and the data can be sampled according to the Nyquist sampling rate. When far-field conditions or the Fresnel approximations do not hold, the spatial frequency band of the scattered field can be estimated by invoking stationary phase arguments and the Nyquist step set accordingly (as shown in [34,35,48]).…”
Section: The Warping Samplingmentioning
confidence: 99%
“…However, here, we consider the determination of the spatial sampling only. This is because optimizing the frequency sampling as well can lead to cumbersome configurations where the spatial positions change for each selected frequency [47]. Therefore, the sampling of the wavenumber band is achieved by employing standard arguments based on the range extent of the area to be imaged, i.e., ∆k 0 = π/n(z max − z min ).…”
Section: The Warping Samplingmentioning
confidence: 99%
“…This problem is exceptionally challenging because it is both nonlinear and ill-posed [8], demanding a substantial number of measurements to attain a satisfactory level of accuracy. Several methodologies have been devised to tackle such complex challenges, including phase retrieval algorithms [9], and optimization techniques [10,11,12,13]. Nonetheless, there remains plenty room for enhancement in terms of computational efficiency, robustness, and adaptability to diverse scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we just extend the analysis to a three-layered background medium, which is relevant in TWRI applications. In particular, we focus in reducing the number of spatial measurements (which generally represents the bulk of measurement time), but the method can be applied to reduce both spatial and frequency measurements [27], although the resulting spatial-frequency measurement grid can be not necessarily convenient.…”
Section: Introductionmentioning
confidence: 99%